The Effects of Prednisolone Treatment on Cytokine Expression in Patients with Erythema Nodosum Leprosum Reactions - Negera, Edessa; Walker, Stephen L.; Bobosha, Kidist; Bekele, Yonas; Endale, Birtukan; Tarekegn, Azeb; Abebe, Markos; Aseffa, Abraham; Dockrell, Hazel M.; Lockwood, Diana N. (Frontiers in Immunology, 2018)
EErythema nodosum leprosum (ENL) is a systemic inflammatory complication occurring mainly in patients with lepromatous (LL) and borderline lepromatous (BL) leprosy. Prednisolone is widely used for treatment of ENL reactions but clinical improvement varies. However, there is little good in vivo data as to the effect of predninsolone treatment on the pro-inflammatory cytokines in patients with ENL reactions. As a result, treatment and management of reactional and post reactional episodes of ENL often pose a therapeutic challenge. We investigated the effect of prednisolone treatment on the inflammatory cytokines TNF, IFN-γ, IL-1β, IL-6 and IL-17 and the regulatory cytokines IL-10 and TGF-β in the skin lesion and blood of patients with ENL and compared with non-reactional LL patient controls. A case-control study was employed to recruit 30 patients with ENL and 30 non-reactional LL patient controls at ALERT Hospital, Ethiopia. Blood and skin biopsy samples were obtained from each patient before and after prednisolone treatment. Peripheral blood mononuclear cells (PBMCs) from patients with ENL cases and LL controls were cultured with M.leprae whole-cell sonicates (MLWCS), phytohaemagglutinin (PHA) or no stimulation for 6 days. The supernatants were assessed with the enzyme-linked immuno-absorbent assay (ELISA) for inflammatory and regulatory cytokines. For cytokine gene expression, mRNA was isolated from whole blood and skin lesion s and then reverse transcribed into cDNA. The mRNA gene expression was quantified on a Light Cycler using real-time PCR assays specific to TNF, IFN-γ, IL-β, TGF-β, IL-17A, IL-6, IL-8, IL-10. The ex vivo production of the cytokines: TNF, IFN-γ, IL-1β and IL-17A was significantly increased in untreated patients with ENL. However, IL-10 production was significantly lower in untreated patients with ENL and significantly increased after treatment. The ex vivo production of IL-6 and IL-8 in patients with ENL did not show statistically significant differences before and after prednisolone treatment. The mRNA expression in blood and skin lesion for TNF, IFN-γ, IL-1β, IL-6 and IL-17A significantly reduced in patients with ENL after treatment, while mRNA expression for IL-10 and TGF-β was significantly increased both in blood and skin lesion after treatment. This is the first study examining the effect of